Temperature-Dependent Activity of Motor Proteins: Energetics and Their Implications for Collective Behavior - Yadav, Saumya; Kunwar, Ambarish (Frontiers in Cell and Developmental Biology, 2021)
Molecular motor proteins are extremely important components of cellular transport system that harness chemical energy derived from ATP hydrolysis to carry out directed mechanical motion inside the cells. Transport properties of these motors such as processivity, velocity and their load dependence have been well established through single molecule experiments. Temperature dependence of biophysical properties of molecular motors are now being probed using single molecule experiments. These experiments in turn have revealed their activation energies and how they compare with the thermal energy available from surrounding medium. In this min-review, we summarize such temperature dependent properties of motor proteins and their implications for collective function during intra-cellular transport.